Energy of interaction between polarons and spatial configuration of bipolaron in two-dimensional systems - Kashirina, N.I.; Kashyrina, Ya.O.; Korol, O.A.; Roik, O.S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2020)
The work is aimed at studying the influence of correlation effects on the interaction energy of two-dimensional (2D) polarons. The two-center configuration of a 2D bipolaron corresponds to a shallow secondary minimum, which occurs when only the correlations associated with the permutation symmetry of the system are taken into account. The correlations associated with the direct dependence of the electron wave function on the distance between electrons lead to stabilization of the one-center configuration, and the secondary minimum corresponding to the two-center configuration disappears. Variational calculations were performed using a multiparameter Gaussian function with correlation multipliers. The ground state energy of a bipolaron is ₂ = –0.542169 ₕ* for η = ε∞/ε₀ = 0, where ε∞ and ε₀ are the high-frequency and static dielectric constants of the crystal, respectively, ₕ* is the effective Hartree energy. The binding energy of the bipolaron was calculated with respect to the double energy of the 2D polaron obtained for the wave function, consisting of 5 Gaussian exponents. The ground state energy of a 2D polaron is ₁ = –0.202366 ₕ* for η = 0. The critical value of the ionicity parameter η corresponds to ηс ≈ 0.2. At η > ηc, the 2D bipolaron breaks up into two 2D polarons. Метою роботи є вивчення впливу кореляційних ефектів на енергію взаємодії двовимірних (2D) поляронів. Двоцентрова конфігурація 2D-біполярону відповідає мілкому побічному мінімуму, який виникає тоді, коли враховуються лише кореляції, пов’язані з перестановочною симетрією системи. Кореляції, зумовлені прямою залежністю хвильової функції електронів від відстані між електронами, призводять до стабілізації одноцентрової конфігурації, а побічний мінімум, який відповідає двоцентровій конфігурації, зникає. Варіаційні розрахунки проводилися із застосуванням багатопараметричних гаусових функцій з кореляційними множниками. Енергія основного стану біполярону становить ₂ = –0.542169 ₕ* для η = ε∞/ε₀ = 0, де ε∞ і ε₀ – високочастотна і статична діелектрична проникність кристала відповідно; ₕ* – ефективна енергія Хартрі. Енергія зв’язку біполярону була розрахована по відношенню до подвоєної енергії 2D-полярону, отриманої для хвильової функції, що складається з 5 гаусових експонентів. Енергія основного стану 2D-полярону становить ₁ = –0.202366 ₕ* при η = 0. Критичне значення параметра іонності η відповідає ηс ≈ 0,2. При η > ηc 2D-біполярон розпадається на два 2D-полярони.